sj-jpg-1-ccn-10.1177_20597002221133183 - Supplemental material for Neuroimaging correlates of syndromal depression following traumatic brain injury: A systematic review of the literature - Lisa N. Richey; Barry R. Bryant; Akshay Krieg; Michael J. C. Bray; Aaron I. Esagoff; Tejus Pradeep; Sahar Jahed; Licia P. Luna; Nicholas T. Trapp; Jaxon Adkins; Melissa B. Jones; Andrew Bledsoe; et al. (SAGE Journals, 2022)
Supplemental material, sj-jpg-1-ccn-10.1177_20597002221133183 for Neuroimaging correlates of syndromal depression following traumatic brain injury: A systematic review of the literature by Lisa N. Richey, Barry R. Bryant, Akshay Krieg, Michael J. C. Bray, Aaron I. Esagoff, Tejus Pradeep, Sahar Jahed, Licia P. Luna, Nicholas T. Trapp, Jaxon Adkins, Melissa B. Jones, Andrew Bledsoe, Daniel A. Stevens, Carrie Roper, Eric L. Goldwaser, LiAnn Morris, Emily Berich-Anastasio, Alexandra Pletnikova, Katie Lobner, Daniel J. Lee, Margo Lauterbach, Simon Ducharme, Haris I. Sair and Matthew E. Peters in Journal of Concussion
Keywords: Emergency Medicine; Medicine; Neurology and Neuromuscular Diseases; Orthopaedics; Sports Medicine; Neuroscience